Upaya Pengembangan Kurikulum Pendidikan Agama Islam Dalam Pembinaan Akhlak Peserta Didik di MA HQ Al-Muthohhirin - Anik Nuzuliati; Muhamad Ansori (https://ejournal.insuriponorogo.ac.id/, 2026)
This study aims to describe the development of the Islamic Religious Education (PAI) curriculum in fostering students’ moral character at MA HQ Al-Muthohhirin. The background of this research is based on the strategic role of the PAI curriculum as an instrument for character building amid social change and the challenges of modern education. This study employs a qualitative descriptive approach with data collection techniques including documentation and interviews. The data sources consist of curriculum documents, syllabi, learning instruments, and Islamic Religious Education teachers as the main informants. The findings indicate that the development of the PAI curriculum at MA HQ Al-Muthohhirin is carried out systematically through contextualization of learning materials, the development of teaching methods based on exemplary behavior and habituation, and the integration of religious activities within the madrasah environment. Moral values are embedded across all PAI subjects and supported by learning strategies that emphasize attitude and character formation. The evaluation system is designed comprehensively by assessing attitudes, knowledge, and skills. Therefore, the development of the PAI curriculum at MA HQ Al- Muthohhirin plays a significant role in supporting sustainable moral development among students.